DIGITALIZATION OF THE ACCOUNTING SYSTEM OF THE ENTERPRISE - Бунда, Ольга М.; Матюха, Микола М. (Journal of Strategic Economic Research, 2024)
One of the most important prerequisites for the development of the global economy is its digital transformation, the main goal of which is the digitalization of all business processes of an enterprise. The priorities for the development of the digitalization of business processes of the enterprise are the digitalization of the accounting system at the enterprise. Important consequences of the digitalization of the accounting system are the efficiency and reliability of information, which ensures the achievement of the strategic goals of the company’s development. The purpose of the study is to consider the main features of the development of digitalization of the accounting system at the enterprise. The main research methods are: observation method, methods of analysis and synthesis, induction and deduction, classification, monographic method, generalization method. The main results of the study. The main directions of digitalization, which characterize changes in the accounting system of the enterprise in modern business conditions, are considered. Existing accounting technologies were studied: specialized accounting programs, enterprise management ERP systems, cloud technologies, Blockchain-technologies. The types of software solutions of the accounting system of the enterprise are systematized. The criteria for choosing a software solution for the company’s accounting system are characterized. It has been proven that the primary task is the security of the software solution’s functioning system against internal and external factors. The need to strengthen information security at the enterprise is highlighted. The protection elements of the software solution for the accounting system of the enterprise are defined. Mutual integration of information management systems with the help of Application Programming Interface is considered. Ways to solve the insecurity of backup copies of databases of the software solution of the accounting system at the enterprise have been investigated. Local and cloud ERP enterprise management systems are characterized. Different ways of using the Stand-Alone ERP enterprise management system are highlighted. The types of solutions of cloud ERP enterprise management systems are presented. Study of the application of Blockchain technologies in the accounting system at the enterprise.